Fatty acid profile of lamb meat from two portuguese autochthonous breeds - Pateiro, Mirian (2019)
In Portugal, sheep and goat meat production accounts for 2.8% of the total meat production in the country; and it is capable of supplying approximately 82% of the domestic demand (INE, 2015). Churra-Galega-Bragançana (CGB) and Bordaleira-entre-Douro-e-Minho (BEDM) are two native breeds of the north of Portugal, classified as endangered lamb breeds. These breeds are exploited for meat production, the former in the Atlantic bio-region and the latter in the Mediterranean area. Production factors, such as breed, have a great influence on nutritional aspects related with the content and quality of fat and fatty acid profile (Frank et al., 2016), which are considered important quality indicators that have a great influence on consumer acceptability (Andersen et al., 2005), especially nowadays as consumers have become increasingly concerned about health and the relationship between meat consumption and saturated fatty acids (Leroy and De Smet, 2019). These autochthonous breeds constitute an important genetic heritage that must be preserved, so assessing their fatty acid profile will allow a correct characterization of these breeds and their products.